Osteocyte function, osteocyte death and bone fracture resistance. - Noble, B; Reeve, J (2000)
The function of the most numerous cell in bone, the osteocyte, has until recently been mysterious and at times controversial. There is now an emerging consensus that osteocytes modulate signals arising from mechanical loading and so direct the appearance and disappearance of bone tissue at the microscopic level, which allows bone as an organ both to grow and to adapt efficiently to the body's mechanical needs for strength with lightness. Osteocytes appear to use some molecular signalling pathways that are familiar from other tissues, such as the generation of nitric oxide and prostaglandins as well as directing cell-cell communication via gap junctions. They may also direct the removal of damaged or redundant bone through mechanisms linked to their own apoptosis or via the secretion of specialised cellular attachment proteins such as osteopontin. Osteocytes possess receptors for parathyroid hormone/parathyroid hormone related peptide and both oestrogen receptors alpha and beta. They also express molecules which in nerve cells are involved with glutamate neuro-transmission. At least some of these receptors and their ligands may regulate osteocyte apoptosis and modulate osteocyte signalling.